Justification of the energy saving mechanism in the agricultural sector - Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Manita, Ihor; Маніта, Ігор Юрійович; Манита, Игорь Юрьевич; Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович (My University, 2021)
EN: Recently, the problem of increasing energy efficiency in the agro-industrial complex and the implementation of energy saving policies for Ukraine becomes particularly relevant. The article noted the most significant problems of analyzing the factors of energy efficient agricultural technologies in modern economic conditions: the development of a systematic scientific and sound approach to the implementation of energy efficient technologies, an analysis of energy efficiency in the agroindustrial complex, the de-velopment and substantiation of recommendations for improving energy efficiency and energy saving, which would take into account the specifics of agricultural production. The causes of the high energy intensity of the products of the agroindustrial complex are determined: the low productivity of livestock enterprises and sowing, the lack of systematic control over the compliance of energy saving, lack of developed measures to ensure energy efficiency and energy saving, development and implementation of low energyintensive technologies, as well as the use of alternative energy sources and secondary energy resources. The structure of the energy intensity of one ton of crop production and animal husbandry in Ukraine is given. The main directions of energy saving in agriculture are identified - organizational, technical, technological, energy, selection and presented activities in the context of each direction. The stages that should undergo the development of renewable energy in our country and the main areas of use of renewable energy sources in the agroindustrial complex are noted. The balance of the needs in the energy resources of the farm is given. To reduce the energy intensity of production processes, new technologies must be widely implemented, and energy saving organizations can be attributed to measures that are highly efficient and require minor costs. It is noted that for the rapid introduction of energysaving activities, it is necessary to develop a number of incentives and find sources of financing. Developed a scheme for stimulating the energy saving system. Reveal the essence of the proposed stimulation methods: coercion, promotion and assistance. RU: В последнее время проблема повышения эффективности энергопотребления в агропромышленном комплексе и реализация политики энергосбережения для Украины становится особенно актуальной. В статье отмечены наиболее значимые проблемы анализа факторов энергоэффективных аграрных технологий в современных экономических условиях: разработка системного научно-обоснованного подхода к внедрению энергоэффективных технологий, анализ эффективности использования энергии в агропромышленном комплексе, разработка и обоснование рекомендаций по повышению энергоэффективности и энергосбережения, которые бы учитывали специфику сельскохозяйственного производства. Определены причины высокой энергоемкости продукции агропромышленного комплекса: низкая производительность животноводческих предприятий и посевных угодий, отсутствие систематического контроля за соблюдением энергосбережения, отсутствие разработанных мероприятий по обеспечению энергоэффективности и энергосбережения, развития и внедрения низко энергоемких технологий, а также использования альтернативных источников энергии и вторичных энергетических ресурсов. Приведена структура энергоемкости одной тонны продукции растениеводства и животноводства в Украине. Определены главные направления энергосбережения в сельском хозяйстве - организационные, технические, технологические, энергетические, селекционные и приведены мероприятия в разрезе каждого направления. Отмечены этапы, которые должно пройти развитие возобновляемой энергетики в нашей стране и основные направления использования возобновляемых источников энергии в агропромышленном комплексе. Приведен баланс потребности в энергоресурсах фермы. Для снижения энергоемкости производственных процессов необходимо широко внедрять новые технологии, а вопросы организации энергосбережения можно отнести к мерам, которые являются высокоэффективными и требуют незначительных затрат. Отмечено, что для быстрого внедрения энергосберегающих мероприятий необходимо разработать ряд стимулов и найти источники финансирования. Разработана схема стимулирования системы энергосбережения. Раскрыта суть предложенных методов стимулирования: принуждения, поощрения и содействия. UK: Останнім часом проблема підвищення ефективності енергоспоживання в агропромисловому комплексі та реалізація політики енергозбереження для України стає особливо актуальною. В статті означено найбільш значимі проблеми аналізу факторів енергоефективних аграрних технологій в сучасних економічних умовах: розробка системного науково-обґрунтованого підходу до впровадження енергоефективних технологій, аналіз стану ефективності використання енергії в агропромисловому комплексі, розробка та обґрунтування реко-мендацій щодо підвищення енергоефективності і енергозбереження, які б враховували специфіки сільсько-господарського виробництва. Визначено причини високої енергоємності продукції агропромислового комплексу: низька продуктивність тваринницьких підприємств та посівних угідь, відсутність систематичного контролю за дотриманням енергозбереження, відсутність розроблених заходів щодо забезпечення енергоефективності і енергозбереження, розвитку та впровадження низько енергоємних технологій та використання аль-тернативних джерел енергії та вторинних енергетичних ресурсів. Приведено структуру енергоємності однієї тони продукції рослинництва і тваринництва в Україні. Визначено головні напрями енергозбереження в сільському господарстві – організаційні, технічні, технологічні, енергетичні, селекційні та наведено заходи в розрізі кожного напряму. Означено етапи, які повинен пройти розвиток поновлювальної енергетики в нашій країні і основні напрямки використання поновлювальних джерел енергії в агропромисловому комплексі. Приведено баланс потреби в енергоресурсах ферми. Для зниження енергоємності виробничих процесів необхідно широко впроваджувати нові технології, а питання організації енергозбереження можна віднести до заходів, що є високоефективними і вимагають незначних витрат. Відзначено, що для швидкого впровадження енергозберігаючих заходів необхідно розробити низку стимулів і знайти джерела фінансування. Розроблено схему стимулювання системи енергозбереження. Розкрито сутність запропонованих методів стимулювання: примушування, заохочення та сприяння.
Обоснование механизма энергосбережения в аграрном секторе
Обґрунтування механізму енергозбереження в аграрному секторі
Keywords: agricultural sector; energy efficient technology implementation; energy saving directions; energy saving system organization; alternative energy sources; аграрный сектор; направления энергосбережения; внедрение энергоэффективных технологий; организация системы энергосбережения; альтернативные источники энергии; аграрний сектор; напрямки енергозбереження; впровадження енергоефективних технологій; організація системи енергозбереження; альтернативні джерела енергії